Pregnant Women's experiences of Birth Preparedness and Complication Readiness in Ghana - Kennedy Diema Konlan; Milipaak Japiong; Kennedy Dodam Konlan (Mashhad University of Medical Sciences, 2019)
Background & aim: Most of the maternal mortalities are preventable when safe maternal healthcare practices adhere to antenatal care. Lack of birth and emergency preparedness is one of several factors contributing to maternal mortalities. Adequate birth preparedness (BP), as well as emergency, and complication readiness (CR) planning can determine the survival rate of a pregnant woman and her unborn neonate. The present study aimed to describe the experiences of pregnant women at Jachie Health Center regarding BP and CR. Methods: In this qualitative study, a phenomenological approach was used for data collection. In-depth interviewing was conducted with a total of 15 pregnant women from Jachie Health Center. The interviews were digitally recorded, transcribed verbatim, reviewed several times, and thematic analysis was performed. NVivo software (version 11) was utilized to manage the data and help with thematic analysis. Results: The pregnant women practiced preparations towards the place of delivery, support person, layette, and warning signs of pregnancy. The majority of the cases were not aware of obligatory preparations in terms of transportation and the need for emergency compatible blood donor prior to delivery. Most of the respondents were not sufficiently prepared for delivery due to poverty and low educational status. Conclusion: The role of community members could include the instruction of pregnant women to attend antenatal clinic to receive education regarding birth preparedness and complications readiness. The district health directorate and public health nurses should train community leaders for the benefits of birth preparedness and complications readiness.